Recurrence of Atrial Myxoma in Pregnancy: Successful Medical Management and Postpartum Resection - Joudi, Noor; Levin, Eleanor; Miller, Paul; Nieman, Koen; Lathi, Ruth; Boyd, Jack; El-Sayed, Yasser Y.; Bianco, Katherine; Khandelwal, Abha (Cardiology and Cardiovascular Medicine, 2021)
Background: Cardiac myxoma in pregnant women is extremely rare; with only 50 cases reported in the literature. Management warrants close consideration of both maternal and neonatal morbidity to optimize outcomes. Case: A 38-year-old pregnant woman with a history of atrial myxoma resection at age 19 and a previous ECHO with no evidence of atrial myxomas presents for cardiac evaluation at 17 weeks gestation. Her imaging demonstrated recurrent atrial myxomas. The patient began on full anticoagulation with enoxaparin to reduce stroke risk and followed closely throughout pregnancy by a multidisciplinary team. She was admitted for labor induction at 35 weeks of pregnancy with delivery of a healthy infant followed, approximately one month postpartum, by successful resection of two areas of recurrent left atrial myxoma combined with tricuspid valve repair. Conclusion: This patient underwent medical management of the myxoma throughout pregnancy and had surgery postpartum. She had an uncomplicated delivery and postpartum course, illustrating that this condition can be managed initially, antepartum and early postpartum, with a medical approach.